Development of a Crafted Malaysian Whistleblowing Policy Disclosure Index - Ahmad, Syahrul Ahmar; Sungip, Noraisah; Paino, Halil; Yunos, Rahimah; Hashim, Fatimah (Advances in Social Sciences Research Journal, 2023)
Though there are legislative provisions to protect whistleblowers, there is still no specific legislation that mandates the implementation of a standardized whistleblowing disclosure among Malaysian companies. This has led to inconsistency of whistleblowing disclosure level among local companies (Ahmad et al., 2018). This study proposes the development of Whistleblowing Policy Disclosure Index (WPDI) specifically for the Malaysian listed companies that could reflect a “best practice” model for establishing sound and comprehensive contents of whistleblowing policy disclosure. Specifically, the whistleblowing disclosure index would be developed by using the guidelines issued by the MCCG (2017), OECD (2011), and the Standards Australia (2003). These three guidelines could pave the way for the development of effective and comprehensive disclosure of corporate whistleblowing policy mainly for local scene. Hopefully, this would then assist regulators to provide effective mechanisms to promote whistleblowing as well as possibly mandates the compulsory implementation of a standardised internal whistleblowing procedure in Malaysian companies to ensure greater accountability and transparency to investors.